2014
DOI: 10.1016/j.celrep.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Dosage-Dependent Regulation of Pancreatic Cancer Growth and Angiogenesis by Hedgehog Signaling

Abstract: Summary Pancreatic cancer, a hypovascular and highly desmoplastic cancer, is characterized by tumor expression of Hedgehog (HH) ligands which signal to fibroblasts in the surrounding stroma that in turn promote tumor survival and growth. However, the mechanisms and consequences of stromal HH pathway activation are not well understood. Here we show that the HH co-receptors GAS1, BOC, and CDON are expressed in cancer-associated fibroblasts. Deletion of two co-receptors (Gas1 and Boc) in fibroblasts reduces HH-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 38 publications
(64 reference statements)
6
100
0
Order By: Relevance
“…This cascade of events ultimately results in the regulation of the corresponding target genes (33). Certain components of the Hh signaling pathway such as PTCH1 and GLI1 are direct transcriptional targets, thus establishing a feedback loop that regulates the level of activity of this pathway (34).…”
Section: Introductionmentioning
confidence: 99%
“…This cascade of events ultimately results in the regulation of the corresponding target genes (33). Certain components of the Hh signaling pathway such as PTCH1 and GLI1 are direct transcriptional targets, thus establishing a feedback loop that regulates the level of activity of this pathway (34).…”
Section: Introductionmentioning
confidence: 99%
“…4). Finally, we looked for the expression of GAS1 in fibroblasts since they are present in the stroma of the CP (Emerich et al 2005a), and a previous report indicated that these cells express GAS1 in the pancreas (Mathew et al 2014). However, we could not observe co-localization of GAS1 with a specific marker for fibroblasts (α-SMA) (Fig.…”
Section: Gas1 Is Expressed In the Stroma Of The Choroid Plexusmentioning
confidence: 99%
“…Last but not least, another crucial signalling pathway worth discussing is the Hedgehog signalling pathway which has a dual role in endocrine pancreatic regeneration [ 117 ]. For instance, Hebrok et al [ 118 ] have shown that Indian hedgehog (Ihh), together with Patched-1 (Ptc-1), a receptor and negative regulator of hedgehog activity, is expressed in pancreatic tissue.…”
Section: Pancreasmentioning
confidence: 99%